Upaya Guru Dalam Mengembangkan Kemampuan Membaca Permulaan Pada Anak Usia Dini (Studi Deskriptif di TK Negeri 03 Kecamatan Dompu) - Arinah Arinah; Ihlas Ihlas; Lukman Lukman (Program Studi Bimbingan dan Konseling, 2023)
This research aims to describe the planning, implementation, approach and evaluation of teachers in improving initial reading skills in Kindergarten 03 Dompu District. This research uses descriptive research methods with a qualitative approach. The results of data analysis show that the planning carried out by the teacher is quite good, the teacher prepares the RKH one day before learning, prepares the class and media according to the theme to be studied. This can be seen only once the teacher invites children to remember the previous day's learning activities, carry out apperception and inform them about the theme of that day. In the implementation of learning, teachers are more dominant in using whiteboards and assignment books compared to other media. The teacher does not use a child-centered approach, only rolling/changing the child's sitting position once every 2 weeks. Then during the evaluation, it was seen that several times the teacher asked the children what activities had been carried out in one learning day and the teacher never informed the children about the learning activities for the next day.